Evaluation Of PT And APTT among Diabetes Mellitus Type2 Patients in Atbara City, Sudan - Mohamed Hashim Fadellala, Eman Zeen Elabdeen Hashim Yassin; Hisham Abdelhamid; Adam A. Mohammed1, Salah M. Mansur; Abdelrahman M. Alfarajabi; Hassan Ibrahim Hussein; Abdelfatah O. KaramAlgani; Ghanem Mohammed Mahjaf; Mosab Nouraldein Mohammed Hamad (My University, 2022)
Abstract: Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. To evaluation of PT and PTT among diabetes mellitus type 2 patients. This is a cross-sectional study with a control group based conducted in Atbara hospital during the period from March to July 2018. The patients were interviewed according to a questionnaire prepared for this purpose. A total of 50 samples were from patients with type2 diabetes mellitus and 50 samples were from healthy persons as control. PT and APTT were measured using semi-automated coagulometry (TECO- COATRON M1, GERMANY). The data was analyzed by SPSS software using an independent t-test. The results show that the mean level of prothrombin time in type 2 diabetic patients was (16.64±3.09 Sec) and of control was (16.7±1.24 Sec), it was none significantly correlated (P value = 0.832) and the mean level activated partial thromboplastin time APTT in type 2 diabetic patients was (38.3±8.7) Sec and of control was (36.2±2.7 Sec), it was none significantly correlated (P. value =0.111). Our study concluded that patients with type 2 diabetes mellitus had no hypercoagulable state due to PT and APTT. Another study with large sample size and many variables to reach another fact.